Gamma-Ray Bursts Observed by the Transiting Exoplanet Survey Satellite: Prompt Optical Counterparts and Afterglows of Swift-XRT-localized Gamma-Ray Bursts - Rahul Jayaraman; Michael Fausnaugh; George R. Ricker; Roland Vanderspek; Geoffrey Mo (The Astrophysical Journal, 2024)
Very few detections have been made of optical flashes contemporaneous with prompt high-energy emission from a gamma-ray burst (GRB). In this work, we present and analyze light curves of GRB-associated optical flashes and afterglows from the Transiting Exoplanet Survey Satellite (TESS). Our sample consists of eight GRBs with arcsecond-level localizations from the X-Ray Telescope on board the Neil Gehrels Swift Observatory (Swift). For each burst, we characterize the prompt optical emission and any observed afterglow, and constrain physical parameters for four of these bursts using their TESS light curves. This work also presents a straightforward method to correct for TESS's cosmic-ray mitigation strategy on 20 s timescales, which allows us to estimate the “true” brightness of optical flashes associated with prompt GRB emission. We also highlight TESS’s continuous wide-field monitoring capability, which provides an efficient means of identifying optical emission from GRBs and characterizing early time afterglow light curves. Based on empirical detection rates from Swift and the Fermi Gamma-ray Space Telescope, up to 10 GRBs per year may fall within the contemporaneous TESS field of view.